2023
DOI: 10.1096/fj.202201187rr
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular HSP90 promotes differentiation of lens epithelial cells to fiber cells by activating LRP1‐YAP‐PROX1 axis

Abstract: Capsular residual lens epithelial cells (CRLEC) undergo differentiation to fiber cells for lens regeneration or tansdifferentiation to myofibroblasts leading to posterior capsular opacification (PCO) after cataract surgery. The underlying regulatory mechanism remains unclear. Using human lens epithelial cell lines and the ex vivo cultured rat lens capsular bag model, we found that the lens epithelial cells secrete HSP90α extracellularly (eHSP90) through an autophagy‐associated pathway. Administration of recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Li et al found that the autophagy-associated pathway regulates the YAP pathway by upregulating and secreting HSP90, thereby promoting the differentiation of LECs into fibroblasts and inducing PCO. 40 Transforming growth factorβ (TGFβ) signalling is also activated after cataract surgery, which can induce epithelial-mesenchymal transition (EMT) and fibrosis through the YAP signalling pathway in the PCO. 39 Many factors, such as calponin, 41 fibroblast growth factor, 16 and mechanotransduction of stress, 42 can promote cell differentiation by activating the YAP/TAZ axis and converting LECs into fibrous cells.…”
Section: Dumentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al found that the autophagy-associated pathway regulates the YAP pathway by upregulating and secreting HSP90, thereby promoting the differentiation of LECs into fibroblasts and inducing PCO. 40 Transforming growth factorβ (TGFβ) signalling is also activated after cataract surgery, which can induce epithelial-mesenchymal transition (EMT) and fibrosis through the YAP signalling pathway in the PCO. 39 Many factors, such as calponin, 41 fibroblast growth factor, 16 and mechanotransduction of stress, 42 can promote cell differentiation by activating the YAP/TAZ axis and converting LECs into fibrous cells.…”
Section: Dumentioning
confidence: 99%
“…Li et al. found that the autophagy‐associated pathway regulates the YAP pathway by upregulating and secreting HSP90, thereby promoting the differentiation of LECs into fibroblasts and inducing PCO 40 . Transforming growth factor‐β (TGF‐β) signalling is also activated after cataract surgery, which can induce epithelial‐mesenchymal transition (EMT) and fibrosis through the YAP signalling pathway in the PCO 39 .…”
Section: Hippo Signalling Pathway In Eye Diseasesmentioning
confidence: 99%